If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -3y = 4 Solving 13 + -3y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -3y = 4 + -13 Combine like terms: 13 + -13 = 0 0 + -3y = 4 + -13 -3y = 4 + -13 Combine like terms: 4 + -13 = -9 -3y = -9 Divide each side by '-3'. y = 3 Simplifying y = 3
| b^2+17b=0 | | 15-y=6 | | t/32=7/16 | | 7v+3=38 | | 150x=(120)(150)+120x | | 3w^2+6w+6=0 | | 8c=2c+24 | | 2-4(2+3a)=-2a+14 | | t=v+k | | 0.5x+2-1.5x=1.5x-6 | | 15x+2y=72 | | 4.3v-6=8+4b+3 | | 5+2*n=7-4*n | | 16t^2+32t+9=0 | | 15+4p=2 | | 145x=(115)(145)+115x | | 6x-7=x+8 | | 2r+44=5r+3r-20 | | y+2z=-9 | | 5+3*n=8-5*n | | 2a+3b=45 | | -7x-24+9x=18 | | 3x-5-5x=4-2x-9 | | 3x-(x+5)=5x-2(x+7) | | 6x-11=2x+15 | | 3x(x^2+8)=0 | | -2(3w+3)=12 | | 12x-7=-3x+5 | | 11+4=8b-13 | | -18-11r=-21 | | 24=-12w | | r-2s=sinx*cosy |